Pengaruh Nilai Tanda dan Nilai Simbol Perilaku Hedonisme Dikalangan Mahasiswa Universitas Maritim Raja Ali Haji - Endang Simanjuntak; Siti Arieta; Sri Wahyuni (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Students who live with modernization have shifted the value of attitude mentality as students who should read, write, research, discuss and become individuals who are rich in knowledge on the college board, but it cannot be said that all students are involved in hedonism. The purpose of this study was to measure the level of hedonism and lifestyle among Umrah students. This study uses a quantitative approach where the X1 indicator is the sign value, the X2 indicator is the symbol value and the Y indicator is Hedonism with a population-based test option and a sample of 7,658 Umrah students divided into 366 students based on research need indicators. The way to get the data is through a research questionnaire, namely using the Google form, then this study uses Jeand Baudriliad's theory about consumption and lifestyle so that the results of this study are a validity test of 366 samples with a grand mean of 60% agree with variable X1 and as many as 233 people or 63% agree with variables X2 and 234 or as much as 63.9% agree with the indicator variable Y, it can be analyzed that data analysis is carried out by grouping into categories and describing the data obtained according to the categories. This study found that the five subjects carried out activities that lead to subject pleasure such as hanging out, shopping, vacations, clubbing besides that the subject has an interest in something that is considered important and wants to be different from the surrounding environment and has hopes that lead to pleasure itself. Factors that can affect the hedonic lifestyle of students is the desire to be different so they do various ways to follow the influence of modernization. Keywords: Lifestyle, Student, Hedonism.